2022
DOI: 10.3389/fbioe.2022.880214
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Composite Nanozymes and Their Pro-Oxidative Role in Therapeutics

Abstract: Nanozymes are inorganic nanostructures whose enzyme mimic activities are increasingly explored in disease treatment, taking inspiration from natural enzymes. The catalytic ability of nanozymes to generate reactive oxygen species can be used for designing effective antimicrobials and antitumor therapeutics. In this context, composite nanozymes are advantageous, particularly because they integrate the properties of various nanomaterials to offer a single multifunctional platform combining photodynamic therapy (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…This approach enables the development of NZs with enhanced catalytic activities, stability, and specificity. The combination of metallic NZs with carbon-based nanomaterials or inorganic nanomaterials has been shown to create hybrid NZs with enhanced catalytic activity [ 150 ]. For instance, Xi et al revealed metal valence state-dependent catalytic properties in metal–carbon-based hybrid NZs [ 151 ].…”
Section: Enzymatic Mechanisms and Multifunctional Roles Of Nz@hydrogelsmentioning
confidence: 99%
“…This approach enables the development of NZs with enhanced catalytic activities, stability, and specificity. The combination of metallic NZs with carbon-based nanomaterials or inorganic nanomaterials has been shown to create hybrid NZs with enhanced catalytic activity [ 150 ]. For instance, Xi et al revealed metal valence state-dependent catalytic properties in metal–carbon-based hybrid NZs [ 151 ].…”
Section: Enzymatic Mechanisms and Multifunctional Roles Of Nz@hydrogelsmentioning
confidence: 99%
“…Nanoenzymes are prepared, size-controlled, and functionally tunable nanomaterials with enzyme-catalyzed properties [ 2 , 11 ]. It has been successfully designed to efficiently and stably mimic the activity of natural enzymes [ 12 ]. As the research on nanoenzymes progressed, their application potentials in anti-inflammatory, antioxidant damage, and cancer therapy have been extensively explored [ 13 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this challenge, significant efforts have been directed toward the development of efficient, streamlined, and rapid pathogen detection methods as well as alternative broadspectrum antibacterial agents or strategies. For instance, certain detection platforms and antibacterial materials that utilize nanomaterials, such as continuous cascade nanozyme biosensors [20], cascade methods based on a natural self-assembled nanozyme [21], a nanozyme-mediated CRISPR-Cas 12a system [22], photothermal therapy (PTT) [23], photodynamic therapy (PDT), and photocatalytic therapy (PCT) [24], are emerging [25]. Recently, nanozyme-based sensing platforms have demonstrated successful applications in the diagnosis of bacteria, viruses, and plasmodium parasites [22,26,27].…”
Section: Introductionmentioning
confidence: 99%